ANALISIS KESETIAAN PELANGGAN BERDASARKAN KOMUNIKASI MEREK DAN KEPRIBADIAN MEREK - Adhie Zoelly, Aurellia Salsabila; Magdalena, Nonie (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
Customer loyalty plays a role in improving customer relationships with brands so that it has an impact on company sustainability. Brand communication and brand personality are one of the factors that encourage customer loyalty. The aim of this research is to confirm previous research models by examine the direct and indirect influence of brand communication and brand personality on customer loyalty. 204 users of the iPhone brand smartphone who had replaced or upgraded their smartphone with an iPhone were again the sample in this study. Data was collected by distributing closed questionnaires via Google Form. Regression with a mediation approach was used in this research as a data analysis method. The research results indicate brand communication and brand personality have a direct and indirect effect on customer loyalty.